SIGN SYSTEM AS AN INFORMATION MEDIA SOLUTION AT CURUG TILU LEUWI OPAT - Wantoro; Tangyong, Andreas Hirditanium (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This paper discusses the implementation of sign system design new at the Curug Tilu Leuwi Opat tourist attraction located in Parongpong, Bandung Barat, Indonesia. Based on observations made directly at the location,sign system which previously existed were in poor condition, such as not being maintained, not clearly visible, inconsistent use of materials, and not representing the identity of the place. The problem is what arises is that tourists often get lost or can’t find out all the facilities and rules that apply because the size of the area owned. The sign system ultimately becomes very important for tourist attractions. The method used is to analyze the characteristics of the place, target audience and field needs. The design of the new sign system at Curug Tilu Leuwi Opat consists of: identification sign system, directions, and regulations (prohibitions & warnings). This new sign system can provide the top solution problems that occurred at Curug Tilu Leuwi Opat